The Biogenesis, Biological Functions, and Applications of Macrophage-Derived Exosomes - Shan, Xiaoxiao; Zhang, Caiyun; Mai, Chutian; Hu, Xuerui; Cheng, Nuo; Chen, Weidong; Peng, Daiyin; Wang, Lei; Ji, Zhaojie; Xie, Ying (Frontiers in Molecular Biosciences, 2021)
Macrophage-derived exosomes have been implicated on the modulation of inflammatory processes. Recent studies have shown that macrophage-derived exosomes contribute to the progression of many diseases such as cancer, atherosclerosis, diabetes and heart failure. This review describes the biogenesis of macrophage-derived exosomes and their biological functions in different diseases. In addition, the challenges facing the use of macrophage-derived exosomes as delivery tools for drugs, genes, and proteins in clinical applications are described. The application of macrophage-derived exosomes in the diagnosis and treatment of diseases is also discussed.